Vitamin D and estrogen-dependent tumors - O.A.Gromova; I.Yu.Torshin; D.E.Frolova; N.P.Lapochkina; A.N.Gromov (IP Berlin A.V., 2018)
Vitamin D is characterized by undeniable antitumor properties that are important for both prevention and treatment of tumor diseases. The results of a systematic analysis of the molecular mechanisms of antitumor effects of vitamin D (inhibition of the Wnt/b-catenin cascade, the transcription factor WSTF) and the results of clinical studies of patients with estrogen-dependent tumors are presented, indicating the promise of combined use of estrogen and vitamin D.